2014
DOI: 10.1371/journal.pone.0113151
|View full text |Cite
|
Sign up to set email alerts
|

The hTH-GFP Reporter Rat Model for the Study of Parkinson's Disease

Abstract: Parkinson disease (PD) is the second leading neurodegenerative disease in the US. As there is no known cause or cure for PD, researchers continue to investigate disease mechanisms and potential new therapies in cell culture and in animal models of PD. In PD, one of the most profoundly affected neuronal populations is the tyrosine hydroxylase (TH)-expressing dopaminergic (DA) neurons of the substantia nigra pars compacta (SNpc). These DA-producing neurons undergo degeneration while neighboring DA-producing cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…The increasing availability of transgenic mice over the past few decades has caused mice to assume a greater role in biomedical science compared to rats. However, the advent of transgenic rats such as this hTH-GFP rat line (Iacovitti et al, 2014) allows for further characterization of OB DA neurons from a different rodent species. This adds to the collective knowledge of the function of OB DA neurons, as well as how these neurons may be affected by neurodegenerative diseases such as PD, and is of particular interest to those in the fields of pathology and neurology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increasing availability of transgenic mice over the past few decades has caused mice to assume a greater role in biomedical science compared to rats. However, the advent of transgenic rats such as this hTH-GFP rat line (Iacovitti et al, 2014) allows for further characterization of OB DA neurons from a different rodent species. This adds to the collective knowledge of the function of OB DA neurons, as well as how these neurons may be affected by neurodegenerative diseases such as PD, and is of particular interest to those in the fields of pathology and neurology.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic hTH-GFP Sprague Dawley rats (Iacovitti et al, 2014) were used for all experiments (Taconic Biosciences, United States). Rats were housed in an animal vivarium facility at Florida State University, exposed to a 12-h light and dark cycle, and provided ad libitum access to food and water.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a strain of Berlin‐Druckrey rats bearing a synuclein gene promoter mutation was identified that results in accumulation of synuclein in the mesencephalic area, striatum, and frontal cortex, with altered dopaminergic neuron electrophysiology . Together with transgenic rats, these provide valuable research tools that can be combined through breeding with other animal models relevant to PD, including transgenic rats that express green fluorescent protein (GFP) exclusively in dopaminergic neurons …”
Section: Genetic Rat Models Of Pdmentioning
confidence: 99%
“…74 Together with transgenic rats, these provide valuable research tools that can be combined through breeding with other animal models relevant to PD, including transgenic rats that express green fluorescent protein (GFP) exclusively in dopaminergic neurons. 75…”
Section: Parkin-ko Ratsmentioning
confidence: 99%